Profile of new Patients attending Psychiatry Out-patient Department at Lumbini Medical College-Teaching Hospital, Palpa - Sharma, B; Devkota, A; Pant, SC (Journal of Psychiatrists’ Association of Nepal, 2018)
Introduction: Study on prevalence of psychiatric disorders in Palpa and nearby districts which lie in western Nepal, is not much studied till date. We therefore conducted this study aiming to see the pattern of psychiatric illness in an Outpatient Department of Lumbini Medical College which is a tertiary care centre located in Palpa district. Material And Method: : This is a retrospective study where outpatient record of all new cases attending the Psychiatry OPD from 29th Oct 2014 to 29th Dec 2014 were studied and statistical analysis were done. The number of new patients were 107. Results: Out of 107 patients, 60.74 % (65)) were females and 39.26 %( 42) were males. Patients of age group 31-40yrs showed the largest proportion (27.49%) followed by age group 41-50yrs (24.29%). Majority cases were illiterate (69.15%) followed by primary level of education (14.95%). The occupation of most of the cases were household work (35.51%) followed by farming (31.77%). Anxiety disorder (27.10%) was the most frequent diagnosis ahead of “Others” (18.69%) followed by depressive disorder (15.88%). Conclusion: Most of the new patients attending the psychiatry OPD of Lumbini Medical College were females, of 31-40 age group and most of the patients suffered from anxiety disorders. J Psychiatrists’ Association of Nepal Vol. 6, No. 2, 2017, Page: 42-44